Assessment of beach-cast cetaceans in Pakistan: implications for conservation and management - Gore, M. A.; Culloch, R. M.; Gray, H. W. I.; Hoelzel, R.; Lockyer, C.; Kiani, M. S.; Waqas, U.; Hussain, B.; Rahim, A.; Shah, A.; Ormond, R. F. G. (J. Cetacean Res. Manage., 2023)
Until recently, little was known about the distribution and species occurrence of marine cetaceans in Pakistani waters, an area which needed to be addressed exigently given its inclusion in the Indian Ocean Whale Sanctuary. Boat-based surveys (2005–09) carried out along the coast of Pakistan identified 12 species of cetaceans. Although these surveys can be very useful for providing information on species presence and distribution, estimates of the age and sex of these groups can be more uncertain. Consequently, this present study undertook complementary beach-based surveys over the same period across all accessible regions of the Pakistani coast and created a community reporting scheme for stranded and beach-cast remains of cetaceans. Tissue samples and/or skeletal material were collected over three years from 37 individual specimens, with DNA successfully extracted from 24. Using molecular techniques, a total of seven species were identified and there was an indication that the majority of the samples were from males. An analysis of teeth collected from 12 beach-cast odontocetes showed an age range between neonatal and 17 years. The results of this study corroborate the presence of species observed during the boat-based surveys and identified a further three species. The data also provide additional information on age and sex. A comparison with similar studies suggests that the stranding rate is low in Pakistan. No mass strandings occurred during the seven year monitoring period. The results indicate that beach-based surveys are effective for gathering data on species presence in regions where resources are limited, the terrain is harsh and availability of data is low. Ultimately, the results of this work will help with assessing the conservation status and management requirements of the region’s cetaceans, both locally and internationally with respect to the Indian Ocean Whale Sanctuary.